Emerging roles of proximal tubular endocytosis in renal fibrosis - Chen, Min; Gu, Xiangchen (Frontiers in Cell and Developmental Biology, 2023)
Endocytosis is a crucial component of many pathological conditions. The proximal tubules are responsible for reabsorbing the majority of filtered water and glucose, as well as all the proteins filtered through the glomerular barrier via endocytosis, indicating an essential role in kidney diseases. Genetic mutations or acquired insults could affect the proximal tubule endocytosis processes, by disturbing or overstressing the endolysosomal system and subsequently activating different pathways, orchestrating renal fibrosis. This paper will review recent studies on proximal tubular endocytosis affected by other diseases and factors. Endocytosis plays a vital role in the development of renal fibrosis, and renal fibrosis could also, in turn, affect tubular endocytosis.